GERAKAN MEMBUDAYAKAN KEGIATAN MEMBACA PADA SISWA KELAS AWAL SEKOLAH DASAR - Fahrur Rozi; Apiek Gandamana (Universitas Negeri Medan, 2018)
ABSTRACTThe purpose of this study was to carry out a movement to cultivate reading activities for students in the early grades of elementary school (SD). Early class learning emphasizes reading and writing learning skills, followed by learning basic skills and how to use them when learning to read and write and learn strategies to become smooth readers and writers. Then in class 3 and above, students use these skills to learn Subject Information, which is reading to study. So it is necessary to do a movement to cultivate reading in early elementary school students summarized through, 1) Making clear rules governing reading culture activities, 2) Socializing the importance of reading to all parties involved in student education, 3) Applying habit of reading in various interesting activities and 4) Cultivating reading activities consistently and continuously.Keywords: Movement, Reading Culture, Elementary School Students